Pengaruh Persepsi Manfaat, Persepsi Keamanan, dan Kepercayaan terhadap Penggunaan Aplikasi OVO pada Mahasiswa Akuntansi (Studi Empiris pada Mahasiswa Akuntansi) - Jasmine Aprilia; Sri Trisnaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The rapid advancement of digital innovation has driven the shift from conventional payment methods to electronic payment methods, including digital wallets such as OVO. As early adopters of technology, college students are the primary user group of these services. This study looks at how perceived usefulness, perceived security, and trust affect the use of the OVO application, using the Technology Acceptance Model (TAM) as a guide. While the TAM provides a structured foundation, this study acknowledges the potential influence of contextual factors such as financial literacy and peer influence that are highly relevant to the college student population but remain underexplored in current models. A quantitative approach based on the positivist paradigm was used, with data collected through a structured questionnaire from 78 accounting students. The analysis used SPSS version 25 and included validity and reliability tests, classical assumption testing, multiple linear regression, and hypothesis testing. The results showed that the three variables, namely, Perceived Benefits (X1), Perceived Security (X2), and Trust (X3), significantly influenced the use of the OVO application both simultaneously and partially. However, the limited sample size and narrow academic background may reduce the generalizability of the findings. Future research should consider a broader and more diverse student population and integrate additional moderating factors to provide a more comprehensive understanding of digital payment adoption behavior.